Functional compartmentalization of Rad9 and Hus1 reveals diverse assembly of the 9‐1‐1 complex components during the DNA damage response in Leishmania. Issue 6 (19th July 2016) - Damasceno, Jeziel D.; Obonaga, Ricardo; Santos, Elaine V.; Scott, Alan; McCulloch, Richard; Tosi, Luiz R. O.
Summary: The Rad9‐Rad1‐Hus1 (9‐1‐1) complex is a key component in the coordination of DNA damage sensing, cell cycle progression and DNA repair pathways in eukaryotic cells. This PCNA‐related trimer is loaded onto RPA‐coated single stranded DNA and interacts with ATR kinase to mediate effective checkpoint signaling to halt the cell cycle and to promote DNA repair. Beyond these core activities, mounting evidence suggests that a broader range of functions can be provided by 9‐1‐1 structural diversification. The protozoan parasite Leishmania is an early‐branching eukaryote with a remarkably plastic genome, which hints at peculiar genome maintenance mechanisms. Here, we investigated the existence of homologs of the 9‐1‐1 complex subunits in L. major and found that LmRad9 and LmRad1 associate with chromatin in response to replication stress and form a complex in vivo with LmHus1. Similar to LmHus1, LmRad9 participates in telomere homeostasis and in the response to both replication stress and double strand breaks. However, LmRad9 and LmHus1‐deficient cells present markedly opposite phenotypes, which suggest their functional compartmentalization. We show that some of the cellular pool of LmRad9 forms an alternative complex and that some of LmHus1 exists as a monomer. We propose that the diverse assembly of the Leishmania 9‐1‐1 subunits mediates functional compartmentalization, which has a direct impact on the response to genotoxic stress. Abstract : The Rad9‐Rad1‐Hus1 (9‐1‐1) complex is a key component of the DNA metabolism in eukaryotes. The protozoan Leishmania express a 9‐1‐1‐homolog clamp, which associate with chromatin and participate in the cellular response to genotoxic stress. LmRad9 and LmHus1‐deficient cells have opposite phenotypes. Remarkably, LmRad9 forms an alternative complex, and LmHus1 exists as a monomer. These alternative forms may mediate the observed functional compartmentalization with a direct impact on the response to genotoxic stress.